2011
DOI: 10.1186/1475-2875-10-165
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodial sugar transporters as anti-malarial drug targets and comparisons with other protozoa

Abstract: Glucose is the primary source of energy and a key substrate for most cells. Inhibition of cellular glucose uptake (the first step in its utilization) has, therefore, received attention as a potential therapeutic strategy to treat various unrelated diseases including malaria and cancers. For malaria, blood forms of parasites rely almost entirely on glycolysis for energy production and, without energy stores, they are dependent on the constant uptake of glucose. Plasmodium falciparum is the most dangerous human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 67 publications
1
28
0
Order By: Relevance
“…PfHT hexose transporter function is known to be required for Plasmodium parasite development in culture and in animal models (14,18,19,25,35). We find that not only does lopinavir directly block glucose uptake into P. falcipa- 3 H]2DOG uptake was determined in the presence of various concentrations of lopinavir and substrate.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…PfHT hexose transporter function is known to be required for Plasmodium parasite development in culture and in animal models (14,18,19,25,35). We find that not only does lopinavir directly block glucose uptake into P. falcipa- 3 H]2DOG uptake was determined in the presence of various concentrations of lopinavir and substrate.…”
Section: Discussionmentioning
confidence: 80%
“…Similar to GLUT1 and GLUT4, the predicted topology of PfHT comprises 12 transmembrane helices, forming a central glucose permeation path. Key residues that are involved in glucose binding and transport are preserved between the human and malaria glucose transporters (14,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, three other putative sugar transporters have been identified in the genome of P. falciparum. However, they show \21% sequence identity compared with PfHT, and their function has not yet been investigated (48).…”
Section: P Falciparum Glucose Transportersmentioning
confidence: 99%
“…Among all these candidates, PfHT1 is the only malarial transporter that has been validated both chemically and genetically (Staines et al, 2010). Gene deletion studies and D-glucose derivatives used as inhibitors confirmed the essential role of the hexose transporters for the asexual parasite development and other parasite stages (Blume et al, 2010, Slavic et al, 2011.…”
Section: Transportersmentioning
confidence: 99%